The effect of thioredoxin and prochymosin coexpression on the refolding of recombinant alpaca chymosin - S. V. Belenkaya; D. N. Shcherbakov; A. I. Chapoval; T. I. Esina; V. V. Elchaninov (Вавиловский журнал генетики и селекции)
The milk-clotting enzyme chymosin is a member of the group of aspartate proteinases. Chymosin is the main component of rennet traditionally obtained from the stomachs of dairy calves and widely used to coagulate milk in the production of various types of cheese. Another source of chymosin, which does not require the killing of animals, is based on recombinant DNA technology. Recombinant alpaca chymosin has a number of valuable technological properties that make it attractive for use in cheese-making as an alternative to recombinant bovine chymosin. The purpose of this work is to study the effect of coexpression of thioredoxin and prochymosin on the refolding of the recombinant zymogen and the activity of alpaca chymosin. To achieve this goal, on the basis of the pET32a plasmid, an expression vector was constructed containing the thioredoxin A gene fused to the N-terminal sequence of the marker enzyme zymogen, alpaca prochymosin. Using the constructed vector, pETTrxProChn, a strain-producer of the recombinant chimeric protein thioredoxin-prochymosin was obtained. The choice of prochymosin as a model protein is due to the ability of autocatalytic activation of this zymogen, in which the pro-fragment is removed, together with the thioredoxin sequence attached to it, with the formation of active chymosin. It is shown that Escherichia coli strain BL21 transformed with the pET-TrxProChn plasmid provides an efficient synthesis of the thioredoxin-prochymosin chimeric molecule. However, the chimeric protein accumulates in inclusion bodies in an insoluble form. Therefore, a renaturation procedure was used to obtain the active target enzyme. Fusion of thioredoxin capable of disulfide-reductase activity to the N-terminal sequence of prochymosin provides optimal conditions for zymogen refolding and increases the yield of recombinant alpaca chymosin immediately after activation and during long-term storage by 13 and 15 %, respectively. The inclusion of thioredoxin in the composition of the chimeric protein, apparently, contributes to the process of correct reduction of disulfide bonds in the prochymosin molecule, which is reflected in the dynamics of the increase in the milk-clotting activity of alpaca chymosin during long-term storage.